Аналитическая психология и психотерапия - Юнг Карл Густав (Хрестоматия по психологии, 2001)
Экземпляры: аб. (2007) / Инвентарный номер: 51254 / Цена: / Сис.шифр: 88.5 / Авт.знак: Ю 50 / ГРНТИ: 15.21.41 / ББК: 88.5я7